Microfiltration and Ultrafiltration Process to Produce Micellar Casein and Milk Protein Concentrates with 80% Crude Protein Content: Partitioning of Various Protein Fractions and Constituents - Prafulla Salunke (Dairy, 2021)
The objective of the study reported in this research paper was to produce micellar casein concentrate (MCC) and milk protein concentrate (MPC) with 80% crude protein relative to total solids (TS) using MF and UF processes respectively. Additionally, capillary gel electrophoresis (CGE) was used to study the protein fractions in retentate and permeate. For MCC production, 227 L of pasteurized SM was subjected to MF using 0.5-micron spiral wound polyvinylidene fluoride membrane. During the process, diafiltration (DF) water was added at six intervals, totaling 100% of the feed volume. For MPC production, 227 L of pasteurized SM from the same lot was subjected to UF using 10 kDa Polyethersulfone membranes. During the process, DF water was added at four different intervals, with a final total addition of 40% of the feed volume. Both processes used a volume reduction of five. There were significant (p < 0.05) differences in all of the compositional parameters, except fat and casein for the MF retentate (MFR) and UF retentate (UFR). UFR had a higher crude protein (CP), TS, lactose, ash and calcium content as compared to MFR and this affected the CP/TS ratio found in both the retentates. The differences in membrane pore sizes, operating pressures and level of DF used all contributed to the differences in final CP/TS ratio obtained. The CGE analysis of individual protein fractions present in the UFR and MFR showed that UFR has a β-lactaglobulin to α-lactalbumin (α-LA) ratio similar to SM, whereas the MFR has a higher ratio, indicating preferential transmission for α-LA by the MF membrane. The results from this study show that MF and UF processes could be used for production of MCC and MPC with similar CP/TS ratio with careful selection of operating parameters, and that CGE can be used for detailed analysis of various protein fractions.